Cognitive Ecology in the Age of the Internet (Nexo Revista Científica, 2020)
The article deals with the problem of intellectual behavior in the era of development of the Internet and social networks. Just as geo-ecology has put the values of nature conservation at the forefront over those of economic gain, so cognitive ecology puts intellectual values at the forefront of the cognitive process. The author substantiates the idea that the Internet has its own cognitive ecology. An overabundance of information requires more complex skills in evaluating and analyzing information, as well as changing value-based intellectual attitudes. It is argued that the theoretical basis for the analysis of cognitive ecology in the Internet age can be the epistemology of virtues, in which various intellectual virtues and vices are studied. The article lists some intellectual virtues and vices that can be demanded when working on the Internet. These intellectual virtues include: open-mindedness, intellectual caution, intellectual courage, intellectual thoroughness, etc.  It is shown that manifestation of intellectual virtues is necessary to navigate in epistemologically “unfriendly” environment of the Internet.